Data Transmission of Digital Grid Assisted by Intelligent Relaying - He, Shuangbai; Yang, Chun; Li, Yuda; Xie, Binyu; Zhao, Jiaqi (EAI Endorsed Transactions on Scalable Information Systems, 2023)
In this paper, we study the relaying and cache aided digital grid data transmission, where the relaying may be equipped by caching or not, depending on specific applications. For both cases, we evaluate the impact of relaying and caching on the system performance of digital grid data transmission through theoretical derivation. To this end, an analytical expression on the outage probability is firstly derived for the data transmission. We then provide an asymptotic expression on the system outage probability. Finally, some simulation results are provided to verify the correctness of the derived analysis on the system performance, and show the impact of relaying and caching on the data transmission of digital grid system. In particular, the usage of caching at the relaying can help strengthen the data transmission performance of the considered system effectively. The results in this paper could provide some reference to the development of wireless transmission and scalable information systems.
Keywords: Digital grid; data transmission; outage probability; analytical expression; asymptotic expression